Penerapan Budaya 5R dalam Upaya Membina Karakter Karyawan Bagian Painting PT Indonesia Thai Summit Plastech - Mia Destia, Mia Destia; Enjang Suherman, Enjang Suherman; Flora Patricia Anggela, Flora Patricia Anggela (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Every company has its own organizational culture and is different. PT INDONESIA THAI SUMMIT PLASTECH is one of the companies that implements the 5R culture. The 5R culture itself is an organizational culture originating from Japan that is made to make improvements in the work environment. The purpose of this study is that the author wants to know more about the analysis of the causes and strategies of implementing the 5R culture in an effort to foster the character of employees of the painting section of PT Indonesia Thai Summit Plastech. Data in this study was obtained from observations, interviews, and documents of PT Indonesia Thai Summit Plastech related to the application of 5R culture. Employees of PT Indonesia Thai Summit Plastech has not fully implemented the 5R culture even though the company has made rules for implementing the 5R culture. This happens because of several obstacles, one of which is the lack of employee awareness about the importance of implementing 5R culture and its influence in the work environment. Strategies that can be carried out in implementing 5R culture in an effort to build character are conducting socialization about 5R culture policies, affirming sanctions for employees who do not implement 5R culture, forming a special 5R culture team and supervising employees, and rewarding employees so as to increase work motivation.